2239. Colorectal Cancer Screening Rates and Outcomes in HIV-Infected and HIV-Uninfected Individuals. (26th November 2018) - Lam, Jennifer; Hurley, Leo; Udaltsova, Natalia; Alexeeff, Stacey; Klein, Daniel; Corley, Douglas; Silverberg, Michael
Abstract: Background: As people with HIV live longer, age-appropriate colorectal cancer (CRC) screening will be an increasingly important component of care. However, it remains unclear whether CRC screening guidelines for the general population, which recommend screening of average-risk persons starting at age 50, are appropriate for people with HIV particularly those with advanced HIV disease. Methods: We compared CRC screening rates and outcomes among HIV-infected and demographically-matched HIV-uninfected subjects in a large integrated healthcare system. Using electronic health records, we identified subjects aged 50–75 years during 2005 to 2016 with no prior CRC screening. We evaluated time to first CRC screen (FIT, sigmoidoscopy or colonoscopy) using Kaplan–Meier estimates, and compared adenoma and CRC prevalence following first sigmoidoscopy or colonoscopy, by HIV status. Adjusted prevalence ratios (PR) accounted for sex, age, race, smoking status, body mass index, and diagnosis of type 2 diabetes or inflammatory bowel disease. Among HIV-infected subjects, we also evaluated whether CD4 count (<200, 200–499, ≥500) was associated with screening outcome. Results: Among 3, 177 HIV-infected and 29, 219 HIV-uninfected CRC screening-eligible subjects, HIV-infected subjects were more likely to be screened within 5 years of health plan enrollment or turning 50 (85.6% vs. 79.1%, P < 0.001). Among those with a sigmoidoscopy or colonoscopy, adenoma was detected in 161 (19.6%) HIV-infected and 1, 498 (22.6%) HIV-uninfected subjects ( P = 0.048) and CRC was detected in 4 (0.5%) HIV-infected and 69 (1.0%) HIV-uninfected subjects ( P = 0.13). We found suggestion of a lower prevalence of adenoma and CRC among HIV-infected subjects, which only reached statistical significance in unadjusted models (unadjusted PR: 0.86, 95% CI: 0.75–1.00, P < 0.049; adjusted PR: 0.89, 95% CI: 0.77–1.03, P = 0.134). Lower CD4 count did not increase likelihood of a positive CRC screening result. Conclusion: In a setting with overall high screening uptake, we found similar adenoma and CRC prevalence in individuals with and without HIV. Our findings suggest that current CRC screening guidelines for the general population are also suitable for the HIV population. Disclosures: M. Silverberg, Gilead: Grant Investigator, Grant recipient.